INTEGRASI LITERASI HALAL DALAM PEMBELAJARAN SAINS: STUDI KASUS PADA ANALISIS KOSMETIK DI SEKOLAH MENENGAH ATAS - Rahmani, Yulpa; Neneng Windayani; Tri Cahyanto (International Journal Mathla’ul Anwar of Halal Issues, 2026)
Cosmetics are an important part of personal care; however, many teenagers do not understand the potential dangers of chemicals in cosmetics and the importance of the halal status of the products they use. This study aims to integrate science literacy and halal literacy in project-based learning for high school students, with a focus on cosmetics analysis. The method used is the Project-Based Learning (PjBL) model, which allows students to examine their personal cosmetic products, identify harmful ingredients, and verify halal status and BPOM registration. Students were then asked to create educational posters regarding the critical halal points of the cosmetics they use. The results showed that the students successfully identified the cosmetic products they use, but no harmful ingredients such as mercury or hydroquinone were found. Additionally, the cosmetic products examined were registered with BPOM, and some of the products had halal certification. The posters created by the students demonstrated high creativity and reflected their understanding of the halal status and the health impacts of cosmetic products. In conclusion, integrating science literacy and halal literacy through the PjBL approach is effective in enhancing students' critical thinking skills, creativity, and awareness of safe and halal cosmetics.